Asthma and pregnancy prevalence in a developing country and their mortality outcomes - Aguilar, Raul; Martinez, Jorge; Turcios, Edgar; Castro, Victor (Journal of Pulmonology and Respiratory Research, 2021)
Background: Latin America has always had high maternal and infant mortality rates. However, the prevalence of asthma in pregnant patients and their outcomes are unknown. We aimed at answering those questions in a developing country’s maternity hospital. Methods: Since January 2011, a cohort of 591 pregnant asthma patients was prospectively recruited for 60 consecutive months. Patients were followed up by a multidisciplinary team until delivery. They were divided into two groups: one of 186 smokers or morbidly obese patients and another of 405 nonobese nonsmokers. Outcomes of mothers and their babies were documented. Results: Out of 57,031 deliveries, the overall estimated prevalence of 591 asthmatic pregnant patients was 1.03%. When adjusted for age standardized prevalence, it turned to 9.2%. With 28 maternal deaths (49 per 100,000 live births). None of these women had asthma. There were also 413 deaths among newborns (7.24/1000 live births). One occurred in the smoker/obese group (5.37/1000 live births) and two in the nonsmoker nonobese group (4.84/1000 live births). The prevalence of asthma during pregnancy seemed lower than in some affluent societies. Overall maternal mortality rates were similar to national figures; however, data on mothers’ mortality with asthma were unexpectedly absent. Conclusion: A multidisciplinary approach and the use of a low-cost inhaled steroid seemed to be the reasons for this. However, infant mortality rate remained high, which could be related to the risk of asthma itself. We believe there’s a worldwide need for agreements on a standardized approach for asthma’s epidemiological surveys, in order to make them comparable.